Analisis Ryakugo Dalam Anime Jujutsu Kaisen Movie 0 Karya Gege Akutami - Agnes Sofiana Putri; Meira Anggia Putri (Universitas Negeri Padang, 2023)
Ryakugo is a word that can be found in everyday life, but sometimes many people still don't know what words are part of ryakugo. Anime is animation from Japan, in anime it is not uncommon to find words in the form of ryakugo. This research aims to explain the formation of the word ryakugo in the anime Jujutsu Kaisen Movie 0 by Gege Akutami. This research type is qualitative research with descriptive methods. In this study, 1 data were found in the ryakugo in the form of zenbu shouryakukei or shortening of the first syllable, 16 data were found in the ryakugo in the form of gobu shouryakukei or abbreviation of the last syllable, 3 data were found in the ryakugo in the form of chuu shouryakukei or abbreviation of the Middle tribe and 1 data were found in the ryakugo in the form kousei youso tanbun ketsugoukei or abbreviation of the middle and last terms.